2005
DOI: 10.1093/nar/gki537
|View full text |Cite
|
Sign up to set email alerts
|

Modulating DNA bending affects NodD-mediated transcriptional control in Rhizobium leguminosarum

Abstract: Rhizobium leguminosarum NodD binds to the nod box of the inducible nod gene nodA as a V-shaped tetramer and bends the nod box. In this work, we show that the nod gene inducer naringenin decreased gel mobility of nod box DNA–NodD complexes by sharpening the NodD-induced DNA bend, which correlated with nodA transcription activation. NodD can induce different DNA bends when the distance between the two half-sites of the nod box was modified, which severely affected NodD-mediated transcriptional control. One or tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 40 publications
(64 reference statements)
1
44
0
1
Order By: Relevance
“…Coinducers typically do not increase promoter affinity but instead activate transcription via a conformational change in the LTTR-DNA complex (11,35,46,64). While NhaR activates gene expression in vivo in response to Na ϩ , K ϩ , or Li ϩ , this cation response has not been reconstituted in vitro (10,22,23,70).…”
mentioning
confidence: 99%
“…Coinducers typically do not increase promoter affinity but instead activate transcription via a conformational change in the LTTR-DNA complex (11,35,46,64). While NhaR activates gene expression in vivo in response to Na ϩ , K ϩ , or Li ϩ , this cation response has not been reconstituted in vitro (10,22,23,70).…”
mentioning
confidence: 99%
“…25) Besides these regulators, it has been reported that some bacterial transcriptional regulators recognize and respond to flavonoids. NodD regulators, which belong to the LysR family and control the transcription of the nod operons involved in the nodulation of Rhzobiales in response to flavonoid signals released by their leguminous hosts, have been characterized in detail, 26) but the domain structure of NodD accommodating the ligand flavonoid and its molecular mechanism for flavonoid recognition and response are not fully understood. It is plausible that the flavonoid-interacting domains in LmrA/QdoR, YetL, and NodD are structurally conserved.…”
Section: Discussionmentioning
confidence: 99%
“…For many LTTRs, including CysB (15), OxyR (33), OccR (1, 31, 69), NocR (31), CatR (52), ClcR (40), and CbbR (18), DNA bending by the protein is more pronounced in the absence of the activating coeffector than in its presence, leading to the suggestion that bending is inversely correlated with gene activation. However, in a few cases, such as MetR (37), DntR (65), and TrpI (57), DNA bending that occurs upon protein binding is unaffected by coeffector addition, and for NodD (14), the bending is in fact increased in the presence of the coeffector. In the cases of CysB (15), TrpI (13), and MetR (37), the affinity of factor binding to target DNA is also increased upon coeffector addition, but this is not true for many of the other proteins.…”
Section: Fig 4 Emsas With Native Argp (Wt) or Its Variants Argpmentioning
confidence: 99%